PENENTUAN HARI LIBUR NASIONAL UMAT KRISTEN DI INDONESIA MENGGUNAKAN ALGORITMA ASTRONOMI MEEUS - Admiral Musa Julius; Rukman Nugraha; I Putu Pudja (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2016)
Astronomically, Easter falls on the first Sunday following the first full moon after the vernal equinox. In Indonesia, Christian holidays including Easter are regulated by the Ministry of Religious Affairs based on the recommendation of Indonesian Church Union (PGI) and Bishops Conference of Indonesia (KWI). This study objective is to formulate a simple time marker by using Meeus Astronomical Algorithm to determine Christian holidays in Indonesian Gregorian calendar. Another objective is to evaluate the Christian holidays on Indonesian calendar between 1960 and 2015. Finally, this study would also provide prediction for future Christian holidays. This study finds out that the Christian holidays on Indonesian calendar are proven as methodologically accurate. It indicates that Meeus Astronomical Algorithm can produce accurate calculation for determining Christian holidays in Indonesia in the future. KEY WORDS:Meeus astronomical algorithm, christian holidays, Indonesian calendar